THE EVOLVING ROLE OF SLOVAK LOCAL GOVERNMENTS IN INTEGRATING MIGRANTS FROM UKRAINE IN SLOVAKIA - Mihálik, Jaroslav (MIGRATION POLICY AND LEGAL RESPONSES, 2025)
This article examines the evolving role of Slovak local governments in integrating Ukrainian migrants following the 2022 Russian invasion. The study traces how local authorities transitioned from providing immediate humanitarian responses to an unprecedented refugee influx toward implementing strategic, long-term integration policies across education, healthcare, employment, and housing sectors. While Slovakia's decentralized governance structure proved essential for delivering initial aid, ongoing integration efforts reveal critical challenges including insufficient institutional capacities, legislative gaps, and coordination deficiencies. This research demonstrates how multi-stakeholder collaboration involving NGOs and international organizations proved crucial in augmenting local governmental capabilities. The empirical analysis identifies best practices in language support, employment facilitation, and educational integration. The findings reveal significant economic benefits of refugee integration, challenging prevalent perceptions of refugees as solely constituting a fiscal burden. However, local integration efforts remain vulnerable to national political instability and fluctuating policy positions. The research underscores the necessity for enhanced inter-institutional collaboration, refined legislative frameworks, and sustained financial and human capital resources to promote social cohesion and achieve effective integration outcomes in Slovakia.